UPAYA MENINGKATKAN HASIL BELAJAR FOREHAND TENIS MEJA DENGAN METODE DRILL PADA PESERTA DIDIK SD - Husain, Asnati Adam; G Simanjuntak, Victor; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to obtain information on efforts to improve learning outcomes with table tennis forehand drill method in class V students of SD Negeri 2 Batu Ampar Kubu Raya Academic Year 2016/2017. The study was conducted with descriptive qualitative method that involves two variables are independent variables and the dependent variable drill method is the result of learning forehand table tennis. Subjects in this study were class V students of SD Negeri 2 ampar stone stronghold district highways totaling 25 students. This research technique uses measurements to test the backboard and test the service by using the validity test instruments whose value is 0.615 and the reliability of the test instrument is 0.738 so that they meet industry standards to be used as a research instrument for data retrieval. Data analysis using percentage. These results indicate there is a learning outcome forehand table tennis with the method drill on learners class V SD Negeri 2 Batu Ampar Kubu Raya, it is proved by the increase of learning skills forehand table tennis is pretty good, which is the first cycle to the average value -rata 67.28 so the increase of 52%. while the average value on the second cycle is 70.6, so the increase of 72%.Â Keywords: Drill method,learning outcomes table tennis forehand,learnes